“Why Didn’t They Teach Us This?” A Qualitative Investigation of Pharmacist Stakeholder Perspectives of Business Management for Community Pharmacists - Braedon Davey; Daniel Lindsay; Justin Cousins; Beverley Glass (Pharmacy, 2023)
Expanding the scope of practice has provided an opportunity to reflect on the business management role of the community pharmacist. This study aimed to determine stakeholder perspectives of what business management skills are required for the community pharmacist, potential barriers impeding changes to management in the pharmacy program or community pharmacy setting, and strategies to improve the business management role of the profession. Purposively selected community pharmacists across two states in Australia were invited to participate in semi-structured phone interviews. A hybrid approach of inductive and deductive coding was used to transcribe and thematically analyse interviews. Twelve stakeholders described 35 business management skills in a community pharmacy, with 13 skills consistently used by participants. Thematic analysis revealed two barriers and two strategies to improve business management skills in both the pharmacy curriculum and community pharmacy. Strategies to improve business management across the profession include pharmacy programs covering recommended managerial content, learning from experience-based education and creation of a standardised mentorship program. There is an opportunity for business management culture change within the profession, and this may require community pharmacists developing a dual thinking process to appropriately balance professionalism and business management.